Evaluating the Survival Rate of Implant-Supported Fixed Prostheses in Partially Edentulous Patients. - Tarik, Baher; Kashif, Rahmah; Ejaz, Tallal; Naseem, Hina Naz; Iqbal, Ayousha; Akhtar, Fahmeed; Naeem, Nabiha (Journal of Neonatal Surgery, 2025)
Background: Implant-supported fixed prostheses have gained popularity as a modality of treatment in the rehabilitation of partially edentulous patients in terms of their good functional and esthetic results. Nevertheless, they have to be evaluated regularly in order to facilitate evidence-based clinical decisions. Objective: To evaluate the survival rate of implant-supported fixed prostheses in partially edentulous patients. Methods: The study was a prospective cohort study that took place in a tertiary care dental teaching hospital and lasted 24 months. A total of 80 patients with partially edentulous patients who were rehabilitated with implant-supported fixed prostheses through consecutive sampling were enrolled. The data were evaluated with the SPSS software. Kaplan-Meier survival analysis was done and compared by the use of the log-rank test, p-value ≤ was taken to be statistically significant. Results: The total 24-month survival of the implant-supported fixed prosthesis was 95%. Four prostheses failed in the follow-up. The Kaplan-Meier analysis established high chances of survival during the follow-up. Statistical significance was not found in terms of survival depending on the location of implant, type of prosthesis, or even smoking status (p > 0.05). Conclusion: Implant-supported fixed prostheses showed good clinical results and high survival rates in partially edentulous patients in the medium term. The findings back the claim that they should be used as a reliable and predictable form of treatment, provided that proper clinical guidelines are adhered to.